The principle of proportionality and its application in the European arrest warrant - Túlio Felippe Xavier Januário (Revista Brasileira de Direito Processual Penal)
The aim of the present essay is to analyze the possibility and eventual necessity of a proportionality test to be accomplished by the executor state, in the scope of the European arrest warrant, as a manner to contain the use of it in cases of less serious crimes. Therefore, we will analyze, initially, the principle of mutual recognition and its basic precept, which is the idea of mutual trust between the Member States, to examine the context of the construction of the European space of freedom, security and justice, as well as the pillars of the creation of the arrest warrant. That being said, it will be possible to diagnose the problem that we are now discussing, which is, the excessive utilization of the instrument to less serious crimes, as well as try to find out possible solutions, among which, the possibility of a control by the Executor State.